Expressive Power of Anti-Violence Legislation: Changes in Social Norms on Violence Against Women in Mexico. (January 2022) - Htun, Mala; Jensenius, Francesca R.
Abstract : We know more about why laws on violence against women (vaw ) were adopted than about how much and in what ways these laws affect society. The authors argue that even weakly enforced laws can contribute to positive social change. They theorize the expressive power of vaw legislation, and present evidence for a cautiously optimistic assessment of current trends on violence against women and the ways that vaw laws affect social norms. Focusing on a time of major legal change related to vaw in Mexico, this article explores trends in behavior and attitudes related to violence by analyzing four waves of the National Survey on the Dynamics of Household Relations (endireh ), which include detailed interviews with thousands of Mexican women. The authors find that over this period, the share of women experiencing intimate-partner abuse declined, attitudes condoning violence shifted, reporting rates rose, and most women learned about legislation to protect their rights. These changes are consistent with the authors' expectations about the expressive power of anti-violence legislation.